The Impact of Digital Financial Literacy on Millennial Investment Behavior in the Post-Pandemic Era - Safuan Hadi; Suharto Suharto; Mochamad Syafii (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study investigates the impact of digital financial literacy (DFL) on the investment behavior of millennials in Indonesia in the post pandemic era. As digital platforms increasingly mediate investment decisions, DFL emerges as a crucial determinant of financial engagement. Using a qualitative descriptive approach, data were collected through in depth interviews with selected millennials who actively utilize digital investment tools. Thematic analysis revealed that individuals with higher DFL demonstrate better decision making, increased awareness of financial risks, and stronger confidence in navigating digital platforms. Conversely, those with lower DFL showed reluctance to invest and were more vulnerable to misinformation and digital fraud. The study highlights the necessity of integrating DFL into formal education and policy initiatives to foster financial inclusion and responsible investment behavior among younger generations. These findings offer practical implications for educators, policymakers, and financial service providers aiming to develop inclusive digital finance ecosystems tailored to youth needs in developing countries.